Additional Capability Being Developed from UNF-ST&DARDS Unified Database: System Analysis and Fuel Cycle Option Analysis. (2nd September 2017) - Peterson, Josh; Olson, Chuck; St. Aubin, Jim; Craig, Brian
Abstract: The Used Nuclear Fuel Storage, Transportation & Disposal Analysis Resource and Data System (UNF-ST&DARDS) is being developed for the U.S. Department of Energy's Office of Nuclear Energy by the national laboratories. An important part of UNF-ST&DARDS is the Unified Database (UDB), which contains information that can support a variety of activities including fuel storage, fuel transportation, and disposal-related system analysis. Currently, the main application of the UDB is to support evaluation of the characteristics of discharged spent nuclear fuel (SNF) from the U.S. commercial reactors. However, because of the extensive amount of data that has been collected and analyzed for UNF-ST&DARDS, there are many more applications that can utilize the UDB including system analysis with the Next-Generation System Analysis Model (NGSAM) and fuel cycle analysis with fuel cycle simulation codes such as ORION. Going forward, NGSAM and fuel cycle transition analysis with ORION integrate UDB data wherever possible in the UDB's development plan. These advances in NGSAM and fuel cycle analysis can be used in conjunction with the UDB to help answer more complex questions about the optimization, utilization, storage, and eventual disposal of SNF.